Evaluation of the cytotoxicity of the Bithionol - cisplatin combination in a panel of human ovarian cancer cell lines. Issue 1 (December 2017) - Ayyagari, Vijayalakshmi; Hsieh, Tsung-han; Diaz-Sylvester, Paula; Brard, Laurent
Abstract Background Combination drug therapy appears a promising approach to overcome drug resistance and reduce drug-related toxicities in ovarian cancer treatments. In this in vitro study, we evaluated the antitumor efficacy of cisplatin in combination with Bithionol (BT) against a panel of ovarian cancer cell lines with special focus on cisplatin-sensitive and cisplatin-resistant cell lines. The primary objectives of this study are to determine the nature of the interactions between BT and cisplatin and to understand the mechanism(s) of action of BT-cisplatin combination. Methods The cytotoxic effects of drugs either alone or in combination were evaluated using presto-blue assay. Cellular reactive oxygen species were measured by flow cytometry. Immunoblot analysis was carried out to investigate changes in levels of cleaved PARP, XIAP, bcl-2, bcl-xL, p21 and p27. Luminescent and colorimetric assays were used to test caspases 3/7 and ATX activity. Results The efficacy of the BT-cisplatin combination depends upon the cell type and concentrations of cisplatin and BT. In cisplatin-sensitive cell lines, BT and cisplatin were mostly antagonistic except when used at low concentrations, where synergy was observed. In contrast, in cisplatin-resistant cells, BT-cisplatin combination treatment displayed synergistic effects at most of the drug ratios/concentrations. Our results further revealed that the synergistic interaction was linked to increased reactive oxygen species generation and apoptosis. Enhanced apoptosis was correlated with loss of pro-survival factors (XIAP, bcl-2, bcl-xL), expression of pro-apoptotic markers (caspases 3/7, PARP cleavage) and enhanced cell cycle regulators p21 and p27. Conclusion In cisplatin-resistant cell lines, BT potentiated cisplatin-induced cytotoxicity at most drug ratios via enhanced ROS generation and modulation of key regulators of apoptosis. Low doses of BT and cisplatin enhanced efficiency of cisplatin treatment in all the ovarian cancer cell lines tested. Our results suggest that novel combinations such as BT and cisplatin might be an attractive therapeutic approach to enhance ovarian cancer chemosensitivity. Combining low doses of cisplatin with subtherapeutic doses of BT can ultimately lead to the development of an innovative combination therapy to reduce/prevent the side effects normally occurring when high doses of cisplatin are administered.